Aging with AIDS: epidemiological profile of AIDS in older adults in Brazil - Flavia Kelli Alvarenga Pinto; Silvana Teresa Neitzke Wollmann; Michele Hubner; Tatiana Rodrigues do Amaral; Flavia Moreno Alves de Souza; Helena Akemi Wada Watanabe (Brazilian Society of Geriatrics and Gerontology, 2024)
Objective: To assess the historical trend of AIDS detection in Brazil and compare the epidemiological characteristics of this condition in older persons versus the adult population. Methods: Cross-sectional descriptive study of AIDS cases reported in Brazil from 2010 to 2019, utilizing the publicly available database provided by the Unified Health System through the Ministry of Health Department of Informatics (DATASUS). The proportion of AIDS cases for older persons and adults was calculated based on epidemiological characteristics, and Pearson's chi-squared test was applied at a 5% significance level to identify differences. Thematic maps displaying AIDS detection rates were created. Results: Overall, 61.43% of those diagnosed with AIDS were male. The AIDS rate among older adults increased by almost 10%, rising from 8.1 cases per 100,000 in 2010 to 8.7 cases in 2019. Among women, the rate remained relatively stable, while there was an increase among men, rising from 11.0 to 12.6 cases per 100,000 men over the period. The Northeast and North regions showed the most significant increases in detection rates from 2010 to 2019: 81.39 and 44.18%, respectively. Female sex, white race, and lower educational attainment were identified as higher risk factors for infection in older adults compared to the adult population. Conclusion: These data demonstrate an increase in cases of AIDS among older adults in Brazil from 2010 to 2019, particularly among men and in the North and Northeast regions. There is a need to enhance sexual health programs for the older population, as well as to train healthcare professionals to address these demands. This includes promoting educational prevention campaigns that take into account the contexts and challenges faced by older adults.